Measurements of dipole and quadrupole polarizabilities of Rn-like Th4+ - Keele, Julie A.; Smith, Chris S.; Lundeen, S. R.; Fehrenbach, C. W. (My University, 2012)
Measurements of the fine structure pattern in high-L, n = 37 Rydberg levels of Th3+ have been extended and improved to allow more precise determinations of the dipole and quadrupole polarizabilities of the Rn-like Th4+ core of the Th3+ Rydberg system. The improved precision is partly due to the recent availability of theoretical calculations that limit the size of higher-order contributions to the fine structure pattern. The measured polarizabilities are αD = 7.702(6) a.u. and αQ = 29.1(1.9) a.u.